Teachers and Teacher Educators Researching Their Practice: A Dually-Purposed Self-Study. Issue 3 (3rd July 2019) - Hamilton, Miriam
ABSTRACT: This paper focuses on a teacher educator's professional learning gained while facilitating teacher research with teachers in Ireland. The teachers were engaged in a teaching portfolio development process, while the teacher educator conducted a concurrent self-study. Qualitative data was gathered and analysed from the teacher interviews, the teacher educator's reflective journaling and critical friend feedback to generate themes related to both teacher educator and teacher learning. New contextualized knowledge about teaching and learning and insights into facilitation skills in collaborative research design emerged as key findings, and this paper illustrates how self-study enables significant learning opportunities for teacher educators willing to co-position themselves as researcher and researched.